Customer’s satisfaction index at Bangi Wonderland Theme Park and Resort: ticketing services - Mohd Jalal, Syazwana (2018)
A study was conducted to determine customer’s satisfaction towards ticketing services at Bangi Wonderland Theme Park and Resort (BWTPR), Selangor. This research was also conducted to identify the socio-demographic characteristics of the customer at BWTPR and identify the relationship between socio-demographics of customers and their satisfaction level towards ticketing services. A total of 105 respondents answered the questionnaire during data collection between April until May 2018. Descriptive analysis, Satisfaction Index (SI) and correlation analysis were used to analyze the data. Results showed that most visitors were more satisfied with the online ticketing services than the counter ticketing services. It was also found that there were relationships between socio-demographic of customers, which are customers’ gender with their satisfaction level towards ticketing services in this theme park. As a recommendation, the management of the ticketing operation should maintain the online ticketing services and improve the counter ticketing services so that customers will have higher satisfaction towards the ticketing service at BWTPR.